Piling Induced Ground Vibration Observation - Abdul Wahid, Abdul Musawir (Universiti Sains Malaysia, 2006)
Vibration due to piling work can cause numerous implications towards buildings and local residents around the area of the piling work. Its impact becomes more crucial if the piling work is done in compact urban locations whereby the buildings and area are densely populated. Five sets of data had been collected in order to determine which kind of waves carries the most significance in term of its magnitude. These data was attained using an instrument called Blastronic Micro Monitor which has been located at five different points of different lengths (20m, 23m, 30m, 39m and 70m) from the vibration source. The results generally show a decay of peak particle velocity (PPV) magnitude over distance in a straight line from the point of vibration source. However the maximum reading were, 9.2 mm/s for radial wave, 3.0 mm/s for transverse wave and 2.2 mm/s for vertical wave. The vibration induced by piling consists mainly of radial wave, transverse and vertical wave. The relationship between these waves and the length from where they were taken is analyzed. The intensity of the vibration is determined by analyzing the vector sum value of the wave. This thesis provides an understanding on how various signals from piling differ with each other in terms of their magnitude.